Analysis of volatile compounds production kinetics: A study of the impact of nitrogen addition and temperature during alcoholic fermentation - Godillot, Joséphine; Baconin, Clara; Sanchez, Isabelle; Baragatti, Meili; Perez, Marc; Sire, Yannick; Aguera, Evelyne; Sablayrolles, Jean-Marie; Farines, Vincent; Mouret, Jean-Roch (Frontiers in Microbiology, 2023)
Among the different compounds present in the must, nitrogen is an essential nutrient for the management of fermentation kinetics, also playing a major role in the synthesis of fermentative aromas. Fermentation temperature is yet another variable that affects fermentation duration and the production of fermentative aromas in wine. The main objective of this study was thus to evaluate the combined effects of nitrogen addition – at the start of the fermentation process or during the stationary phase – at different fermentation temperatures on both fermentation kinetics and aroma synthesis kinetics. To study the impact of these 3 parameters simultaneously, we used an innovative transdisciplinary approach associating an online GC MS system with an original modeling approach: a Box-Behnken experimental design combined with response surface modeling and GAM modeling. Our results indicated that all three factors studied had significant effects on fermentation and aroma production kinetics. These parameters did not impact in the same way the different families of volatile compounds. At first, obtained data showed that reduction of ester accumulation in the liquid phase was mainly due to important losses by evaporation but also to modifications of yeast metabolic capabilities to synthetisesynthetize these compounds. In a noticeable way, optimal temperature changed for liquid accumulation of the two classes of esters – 23°C for acetate ester and 18°C for ethyl esters – because biological impact of temperature was different for the two chemical families. Moreover, the study of these three factors simultaneously allowed us to show that propanol is not only a marker of the presence of assimilable nitrogen in the medium but above all a marker of cellular activity. Finally, this work enabled us to gain a deeper understanding of yeast metabolism regulation. It also underlines the possibility to refine the organoleptic profile of a wine by targeting the ideal combination of fermentation temperature with initial and added nitrogen concentrations. Such observation was particularly true for isoamyl acetate for which interactions between the three factors were very strong.